The Reporting Quality of Systematic Reviews and Meta-Analyses in Industrial and Organizational Psychology: A Systematic Review - Schalken, Naomi; Rietbergen, Charlotte (Frontiers in Psychology, 2017)
Objective: The goal of this systematic review was to examine the reporting quality of the method section of quantitative systematic reviews and meta-analyses from 2009-2016 in the field of industrial and organizational psychology with the help of the Meta-Analysis Reporting Standards (MARS), and to update previous research, such as the study of Aytug et al. (2012) and Dieckmann et al. (2009). Methods: A systematic search for quantitative systematic reviews and meta-analyses was conducted in the top 10 journals in the field of industrial and organizational psychology between January 2009 and April 2016. Data were extracted on study characteristics and items of the method section of MARS. A cross-classified multilevel model was analyzed, to test whether publication year and journal impact factor (JIF) were associated with the reporting quality scores of articles. Results: Compliance with MARS in the method section was generally inadequate in the random sample of 120 articles. Variation existed in the reporting of items. There were no significant effects of publication year and journal impact factor (JIF) on the reporting quality scores of articles. Conclusions: The reporting quality in the method section of systematic reviews and meta-analyses was still insufficient, therefore we recommend researchers to improve the reporting in their articles by using reporting standards like MARS.